PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS DENGAN PENDEKATAN SPRINGATE (S-SCORE) - Ayundasari, Vina; Kurniawati, Eris Tri (Program Studi Ekonomi Pembangunan, 2024)
Prediction analysis results financial distress can be used to minimize losses for internal or external parties as a result of bankruptcy experienced by the company, as well as predicting the continued existence of the company concerned. The aim of this research is to analyze the influence of liquidity ratios, profitability ratios, non-performing credit ratios and effectiveness ratios on financial distress. The population in this research is Sharia People's Financing Banks (BPRS) in East Java which are registered with the Financial Services Authority in 2018-2022. The data analysis method for this research uses panel data regression analysis. Based on research results regarding the influence of liquidity ratios, profitability ratios, non-performing credit ratios and effectiveness ratios on financial distress at BPRS in East Java. The liquidity ratio has a positive and insignificant effect on financial distress. The profitability ratio has a positive and significant effect on financial distress. The non-performing loan ratio has a negative and insignificant effect on financial distress. The effectiveness ratio has a negative and significant effect on financial distress.